1986
DOI: 10.1021/np50045a025
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites from Chilean Baccharis species

Abstract: Baccharis linearis Ruiz et Pav, Baccharis rbomboidalis Remy, and Baccharis solieri Remy (Compositae). The ethanolic extracts afforded a novel chromene 1 along with seventeen known compounds (Table 1).Chromenes are of common occurrence in the Compositae (1), and the methyl ester of compound 1 was recently reported from a Wemeria species (2). In addition to chromene 1, oleanolic acid, stigmasterol, ß-amyrin, and friedelinol were also present in varying amounts in the three Baccharis species (Table 1). EXPERIMENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
18
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 10 publications
7
18
0
3
Order By: Relevance
“…The spectral characteristics (MS, UV, 1 H-and 13 C-NMR) were identical with published data, for DMCB as published by Labbe et al [31] and for DCEPB as published by Boudourova-Krasteva et al [26].…”
Section: 2-dimethyl-6-carboxyethenyl-2h-benzopyran (Dmcb) and 22-dsupporting
confidence: 82%
See 1 more Smart Citation
“…The spectral characteristics (MS, UV, 1 H-and 13 C-NMR) were identical with published data, for DMCB as published by Labbe et al [31] and for DCEPB as published by Boudourova-Krasteva et al [26].…”
Section: 2-dimethyl-6-carboxyethenyl-2h-benzopyran (Dmcb) and 22-dsupporting
confidence: 82%
“…49 mg of pure A III were isolated (50%), spectral data (UV, IR, 1 H-and 13 C-NMR) were identical with those published by Labbe et al [31].…”
Section: 2-dimethyl-6-carbethoxyethenyl-2h-benzopyran (A III )supporting
confidence: 73%
“…Visto que no Brasil a colheita de própolis pode se dar durante todo o ano, não são raras as possíveis variações sazonais em sua composição e atividade, considerando-se a região e o local de colheita onde a própolis foi produzida (LABBE et al, 1986;SFORCIN et al, 1998).…”
unclassified
“…Phytochemically, it is reported that Baccharis spp. are composed basically by diterpenoids, triterpenoids, flavonoids, and chromenes (Bohlmann et al, 1979;Labbe et al, 1986;Zdero et al, 1988;Jarvis et al, 1991;Verdi et al, 2005) biological activity. Based on a systematic study aiming the characterization of bioactive compounds from Brazilian flora (Grecco et al, 2010;Lago et al, 2010), the present work was undertaken to determine the activities of CH 2 Cl 2 and EtOAc partition phases as well as their purified derivatives obtained from EtOH extract of aerial parts from Baccharis uncinella DC against inflammation induced by the proinflammatory phospholipase A2 (PLA2) and by carrageenan.…”
Section: Introductionmentioning
confidence: 99%